Development of ICT-Based Teaching Materials on Phylogeny Topic as Innovations in Evolution Courses: A need analysis - Akram Akram; Ixora Sartika Mercuriani (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to collect and analyze the data needed for the development of ICT-based teaching materials in evolution courses on phylogeny topic. The methods used are systematic reviews and surveys. Based on the results of a systematic review, it can be concluded that the trend of research on evolution courses on phylogeny topic in scientific articles published in 2015-2021 is the mastery of tree thinking skills. The teaching materials developed to support the mastery of tree thinking skills are booklets, modules, and game cards.Â  Based on the results of the survey, it can be concluded that the majority of students prefer to use smartphones instead of laptops to find and study evolution lecture materials and only a small percentage of students who have obstacles to accessing the internet both in the classroom and outside campus. The highest percentage of electronic teaching materials that students like the most are more diverse teaching materials. This need analysis provides information that can be used to develop ICT-based teaching materials on phylogeny topic